Safe ultrasound-guided percutaneous tracheostomy in eight steps and necessary precautions in COVID-19 patients - MENEGOZZO,CARLOS AUGUSTO METIDIERI (2022)
ABSTRACT Percutaneous tracheostomy has been considered the standard method today, the bronchoscopy-guided technique being the most frequently performed. A safe alternative is ultrasound-guided percutaneous tracheostomy, which can be carried out by the surgeon, avoiding the logistical difficulties of having a specialist in bronchoscopy. Studies prove that the efficacy and safety of the ultrasound-guided technique are similar when compared to the bronchoscopy-guided one. Thus, it is of paramount importance that surgeons have ultrasound-guided percutaneous tracheostomy as a viable and beneficial alternative to the open procedure. In this article, we describe eight main steps in performing ultrasound-guided percutaneous tracheostomy, highlighting essential technical points that can reduce the risk of complications from the procedure. Furthermore, we detail some precautions that one must observe to reduce the risk of aerosolization and contamination of the team when percutaneous tracheostomy is indicated in patients with COVID-19.